DEALING WITH CRITICAL INCIDENTS: EXPERIENCES OF TURKISH NOVICE EFL TEACHERS - Çukur, Hatice Saliha (LLT Journal: A Journal on Language and Language Teaching, 2022)
Moments causing teachers to stop and think about their teaching are called critical incidents and reflecting on them can be a way of gaining insights into their practices and contexts. However, critical incidents are underexplored in the Turkish EFL context. Thus, this qualitative case study aimed to understand the types of critical incidents encountered by six Turkish novice EFL teachers who all graduated from the same English language teaching program, their ways of dealing with these, and how this affected them. Data obtained from reflective journals and a focus group interview were analysed thematically. The results revealed critical incidents related to multiple sources, mainly due to students’ behaviors. Moreover, teachers' strategies varied from addressing the student to acting as the authority. These critical incidents affect novice teachers in various ways, such as questioning their language teacher education and teaching competence, which were discussed in this study along with implications and directions for future studies.